A systematic review on factors associated with health-related quality of life among chronic obstructive pulmonary disease patients - Yahya, Nor Farahain; Omar, Noraida; Daut, Ummi Nadira; Adznam, Siti Nur'asyura; Mohd Yusof, Barakatun Nisak (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Health-Related Quality of Life (HRQOL) is an important data in managing Chronic Obstructive Pulmonary Disease (COPD). Therefore, it is essential to determine factors that associated with HRQOL and identify the gaps for future research. A systematic search using PubMed, Science Direct and Scopus was performed to discover factors that could impact HRQOL among COPD patients. Socio-demographic factors like age, gender, educational level, smoking status, income were found associated with HRQOL. Other factors included Body Mass Index (BMI), comorbidities, sleep quality and exercise capability also could influence HRQOL of COPD patients. Other than that, lung function, dyspnea and exacerbation also found closely related with HRQOL. However, future study is needed to explore more factors such as nutritional status. Besides that, the finding only focused on general population and very little information on elderly population.